100 best parliamentary speeches 1947 - 1997 - Kashyap, Subhash C. (ed.) (New Delhi, 1998)
This book presents some of the most memorable parliamentary speeches delivered by them during the last fifty years (1947-1997). The book opens, quite appropriately, with Pandit Jawaharlal Nehru's historic speech on the Objectives of the Constitutions and Ndia's Tryst with Destiny' delivered on the floor of the Constituent Assembly in 1947..
Keywords: Parliamentary speeches 1947 - 1997